Hydrophilic interaction liquid chromatography in the separation of glycopeptides and their isomers - Kozlik, Petr; Goldman, Radoslav; Sanda, Miloslav (Analytical and bioanalytical chemistry, 2018)
The analysis of intact glycopeptides is a challenge because of the structural variety of the complex conjugates. In this work, we used separation involving hydrophilic interaction liquid chromatography using a superficially porous particle HALO® penta-HILIC column with tandem mass spectrometric detection for the analysis of N-glycopeptides of hemopexin. We tested the effect of the mobile phase composition on retention and separation of the glycopeptides. The results indicated that the retention of the glycopeptides was the combination of partitioning and adsorption processes. Under the optimized conditions, our HILIC method showed the ability to efficiently separate the glycoforms of the same peptide backbone including separation of the isobaric glycoforms. We achieved efficient separation of core and outer arm linked fucose of bi-antennary and tri-antennary glycoforms of the SWPAVGNCSSALR peptide and bi-antennary glycoform of the ALPQPQNVTSLLGCTH peptide, respectively. Moreover, we demonstrated the separation of antennary position of sialic acid linked via α2-6 linkage of the monosialylated glycopeptides. Glycopeptide isomers are often differentially associated with various biological processes. Therefore, chromatographic separation of the species without the need for an extensive sample preparation appears attractive for their identification, characterization, and reliable quantification.
Keywords: Glycopeptides; Chromatography, Liquid; Humans; Tandem Mass Spectrometry; Proteomics; Hydrophobic and Hydrophilic Interactions; Hydrophilic interaction liquid chromatography; lidé; hemopexin; Glycoproteomics; proteomika; Hemopexin; tandemová hmotnostní spektrometrie; Amino Acid Sequence; chromatografie kapalinová; Isomerism; LC-MS/MS; isomerie; hydrofobní a hydrofilní interakce; glykopeptidy; sekvence aminokyselin